Applicability of freeze-thaw resistance testing methods for high strength concrete at extreme −52.5 °C and standard −18 °C testing conditions. (June 2018) - Bumanis, Girts; Dembovska, Laura; Korjakins, Aleksandrs; Bajare, Diana
Graphical abstract: Highlights: Freeze-thaw resistance of high strength concrete (HSC) with supplementary cementitious materials was determined. 5% NaCl solution saturated HSC were compared under standard −18 °C and extreme −52.5 °C testing conditions. Similar results were obtained by reducing the testing time from 150 to 12 freeze-thaw cycles. Ultrasonic pulse velocity and weight change proved to be promising methods for indicating structural and strength changes. Silica fume reduced freeze-thaw resistance of HSC comparedto both reference and metakaolin containing HSC compositions. Abstract: In the present paper an attempt was made to evaluate reliability and efficiency of two freeze-thaw testing methods by testing high strength concrete (HSC) with two different supplementary cementitious materials as a partial substitute to cement in binary blend. Silica fume (SF) or metakaolin containing by-product (MKW) was used replacing with them 5, 10 or 15 wt% of cement. The freeze-thaw resistance of HSC samples saturated with 5% NaCl solution was tested at standard −18 °C and extreme −52.5 °C testing conditions. HSC series with SF exhibited higher initial strength, while poor resistance against freeze-thaw cycles was observed. Strength loss from 8 to 25% was observed after 12 freeze-thaw cycles at −52.5 °C, while 15 cycles reduced the strength by 30 to 53%, which was similar to 110 or 150 freeze-thaw cycles at −18 °C. Hence, it was concluded that extreme low temperature testing can significantly reduce the time, which is necessary for evaluating freeze-thaw durability of HSC. HSC without air entraining additives with W/C ranging from 0.38 to 0.45 proved to be vulnerable to freeze-thaw exposure as its water absorption gradually increased. Ultrasonic pulse velocity measurements during freeze-thaw tests allowed to determine indirectly the strength loss and good correlation between the two was observed.